Connecting electrodes with light: one wire, many electrodes12. Issue 12 (7th September 2015) - Choudhury, Moinul H.; Ciampi, Simone; Yang, Ying; Tavallaie, Roya; Zhu, Ying; Zarei, Leila; Gonçales, Vinicius R.; Gooding, J. Justin
Abstract : The requirement of a wire to each electrode is central to the design of any electronic device but can also be a major restriction. Herein it is shown how electrodes can be connected using light such that a multielectrode device requires only a single physical wire. Abstract : The requirement of a wire to each electrode is central to the design of any electronic device but can also be a major restriction. For example it entails space restrictions and rigid device architecture in multi-electrode devices. The finite space that is taken up by the array of electrical terminals and conductive pads also severely limits the achievable density of electrodes in the device. Here it is shown that a travelling light pointer can be used to form transient electrical connections anywhere on a monolithic semiconductor electrode that is fitted with a single peripheral electrical terminal. This is achieved using hydrogen terminated silicon electrodes that are modified with well-defined organic monolayers. It is shown that electrochemical information can be either read from or written onto these surfaces. Using this concept it is possible to form devices that are equivalent to a conventional electrode array but that do not require a predetermined architecture, and where each element of the array is temporally "connected" using light stimulus; a step change in capability for electrochemistry.